Assessing patients' know ledge, attitude and practice with coronary artery diseases and one of their family's member about theraputic regimen advises (Tehran University of Medical Sciences, 2000)
"nThis reasearch is a discriptive study. the purpose of this study was to assess"npatients' knowledye , attitude and practice with coronary artery diseases and of their family . member about theraputic Regimen advises . In this study , 50 patients with Coronary artery diseases and 50 members of their family have been studied randomly . Two questionnaires were prepared, one for patients and another for their families, which both of them included 4 parts as follows : Demographic data, question related to knowledge, the kind of attitude and quality of practice ."nThen the Scores of patients > knowledge and also their family's were determined Separately and the relation ship between their variables together in patients with their family w&s measured."nThe results of investigation showed that, most percentage of patients and their family possesing high knowledge and positive attitude about theraputic regimen and most percentage of patients have had disireable practice and their families have had non - disireable practice."nThe results showed that there was a significant relation between patients >"nknowledge and their attitude , and between their familys > practice and their attitude.